PENGARUH TINGKAT PENDAPATAN, TINGKAT KEPERCAYAAN DAN SOSIALISASI PERPAJAKAN DALAM MENENTUKAN KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN - Hardiman Aritonang; Erni Yanti Natalia (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
This research aims to determine the influence of income level, level of trust, and tax socialization in deciding compliance with land and building tax payments in Batam City. The population in this study were all PBB taxpayers in Batu Aji District. This research uses primary data with a purposive sampling method. Based on the Slovin formula, the number of samples or respondents was 100. The research results show that partially the level of income does not have a significant effect, but the level of trust and socialization of taxation has a significant impact in determining compliance with paying PBB. Simultaneous results of income level, level of trust, and tax socialization significantly influence compliance with land and building tax payments. Keywords: Compliance, Income Level, Level of Trust and Tax Socialization